Alison a stunning and emotional graphic novel for fans of Sally Rooney, from an award winning illustrator and author - Stewart, Lizzy 1985- (Serpent's Tail, 2023)
"This graphic novel chronicles the fictional life story of Alison Porter, whose talent as a painter blossoms in bohemian 1970s London. Alison tells the story of a young British woman who, in her twenties, seizes upon the opportunity to escape from her quiet life in Dorset to the thrumming art scene of late-1970s London. But the vehicle for her escape is a charismatic older man whose reputation as an artist and philanderer casts a shadow which will follow Alison for years as she pursues her painting career. Combining immaculate prose and stunning artwork, Alison is a complex love and coming-of-age story, as well as a meditation on female friendship and empowerment, class and patriarchy, the creative process and the thorny world of fine art. British illustrator and author Lizzy Stewart crafts a graphic novel that evokes the atmospheric milieu of bohemian London in the late 20th century, while at the same time exploring the more universal struggles of women who must navigate male-dominated spaces."--Publisher
Keywords: Geschichte 1970-1979; Künstler; Feminismus; Beziehung; Junge Frau; Patriarchat; Malerei; London; Comic